The Effect of the Lottery Card Method on Discovery Learning Assisted by Video Learning Media on Student Learning Outcomes - Nur Azizah; Tri Santoso; Dewi Satria Ahmar; Magfirah Magfirah; Meida Esterlina Marpaung (MASI Mandiri Edukasi, 2026)
This study aims to describe the effect of the lottery card method on student learning outcomes in acid-base solution material during video-assisted discovery learning. This study used a pre-test and post-test control group design. The study population consisted of all 247 ninth-grade students at SMA Negeri 5 Palu, across eight classes. Two classes were selected as samples, namely class XI Merdeka 5 (control) and class XI Merdeka 6 (experimental), each with the same number of 34 students, using simple random sampling. Data were collected using pre-tests and post-tests. The control class used only the discovery learning model, while the experimental class used the lottery card method in video-assisted discovery learning. From the analysis results, the N-ngai score for the control class was 0.49, and for the experimental class was 0.67, both of which were classified as moderate. Although both were moderate, the N-ngai score for the experimental class was higher than that for the control class. The t-test results showed a significance value of 0.001, which is less than 0.05, so it can be concluded that Ho is rejected and Ha is accepted. Therefore, it can be said that the lottery card method in discovery learning assisted by video media has an effect on student learning outcomes in acid-base solution material.